Cadmium-induced turion formation of Spirodela polyrhiza (L.) Schleiden - Oláh, Viktor; Hepp, Anna; Lakatos, Gyula; Mészáros, Ilona (Acta Biologica Szegediensis, 2014)
Spirodela polyrhiza (L.) Schleiden (giant duckweed) is an extensively studied representative of duckweeds (Lemnoideae subfamily, Araceae). Despite its widespread application in numerous research areas and well-known capability for producing turions, the effects of various toxicants on turion production are sporadically discussed in the scientific literature. Our aim was to study the growth of S. polyrhiza under cadmium stress and to test its potential interference with turion production. Effects of cadmium were assessed in axenic cultures of a local S. polyrhiza clone in 7-days-long duckweed growth inhibition tests. Our results indicated that higher cadmium concentrations decreased the relative growth rates of cultures within 3 days and growth inhibition reached its maximum between the 3rd and 5th days with 0.080 mg l-1 IC50. Parallel with slowed frond production - by mirror image pattern - induction of turion formation was observed. The first turions protruded by the 5th day of treatments in the 0.075-0.75 mg l-1 concentration range. Such rapid onset of turion formation is indicative of an almost immediate switch between normal and turion mode of meristem function upon cadmium stress. The consideration of this mechanism in practical applications of S. polyrhiza is recommended.